Research on the influence of vertical deflection to the line geodetic network - prism method - Jasmin Taletović; Dževad Krdžalić (Geodetski Glasnik, 2017)
This work was carried out calculating and research the deflection of the vertical on line traverse in the geodetic network of the City of Sarajevo. Determination of vertical deflection is done using Quadar. Computations consist of two segments. The first segment is the calculation of the coordinates of points without taking into account the vertical deflection, while the second segment dealt with the calculation of the coordinates of points by taking into account the vertical deflection.